2022
DOI: 10.1002/marc.202200681
|View full text |Cite
|
Sign up to set email alerts
|

Tannic Acid Crosslinked Self‐Healing and Reprocessable Silicone Elastomers with Improved Antibacterial and Flame Retardant Properties

Abstract: Silicone elastomers are widely used in aviation, electronics, automotive, and medical device fields, and their overuse inevitably causes recycled problems. In addition, the elastomers are subject to attack by bacteria and fire during use in some application scenarios, which is a safety hazard. Therefore, there is a great need to prepare silicone elastomers with improved antibacterial, flame retardant, self-healing, and recyclable functions. A new strategy is proposed to prepare silicone elastomers with bio-bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 54 publications
0
9
0
Order By: Relevance
“…Upon increasing the temperature from 30°C to 150°C, a significant enhancement in the transmission peaks of C=O groups engaged in hydrogen bonding within urea and urethane was observed. There was also a gradual increase in N‐H stretching vibrations associated with hydrogen bonds 31 . These observations suggested the occurrence of a dissociation mechanism for hydrogen bonds within the rigid domain as temperature increased.…”
Section: Resultsmentioning
confidence: 85%
See 3 more Smart Citations
“…Upon increasing the temperature from 30°C to 150°C, a significant enhancement in the transmission peaks of C=O groups engaged in hydrogen bonding within urea and urethane was observed. There was also a gradual increase in N‐H stretching vibrations associated with hydrogen bonds 31 . These observations suggested the occurrence of a dissociation mechanism for hydrogen bonds within the rigid domain as temperature increased.…”
Section: Resultsmentioning
confidence: 85%
“…PDMS 3 ‐IPDI 4 ‐SS‐F and its corresponding D‐A crosslinking product, PDMS 3 ‐IPDI 4 ‐SS‐F‐M, were further characterized using FTIR spectra, as depicted in Figure S2. The absence of the absorption peak at 2260 cm −1 suggested that the complete reaction had occurred for ‐NCO 31 . The appearance of a new peak at 1722 cm −1 indicated the presence of D‐A covalent bonds in the crosslinking product PDMS 3 ‐IPDI 4 ‐SS‐F‐M 27 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…High-performance antimicrobial and antifouling materials with an in-built ability to recover mechanical strength can be used as fouling-release and corrosion-resistant polymer coatings. For example, flame retardant, self-healing and recyclable hybrid materials with >90% antimicrobial efficiency were obtained with PDMS, 2,2-bis(hydroxymethyl)propionic acid as the intermediate chain extender and crosslinked by interactions with tannic acid that is a natural antimicrobial substance [ 97 ]. The products exhibited good mechanical and tensile properties, with σ max up to 7.5 MPa and ε max up to 1540%.…”
Section: Smart Applications Of Self-healing Polysiloxanesmentioning
confidence: 99%